Enlightenment and the gasping city : Mongolian Buddhism at a time of environmental disarray - Abrahms-Kavunenko, Saskia (Cornell University Press, 2019)
"A timely exploration of how human beings experience their increasingly degraded environments, this book demonstrates how the pollution of the air, with its attendant limitations on light and breath, creates obscurations both cosmologically and materially for the residents of Ulaanbaatar, and how these blockages reside in a dynamic relationship with light, purification and enlightenment."